Failure pressure prediction of pipelines steel in the presence of corrosion defects and pre-strain - Prakash Raj, Subramaniam (2013)
This projects explains the methods used in predicting the failure pressure of defective pipelines. The failure pressure of defective was estimated for the pipe with the different types of defects. APIX42 steel is chosen for this studies and it must undergoes few machining steps to design a tensile test specimen according to ASTM E8-08M-11. Data obtained from tension test (engineering stress strain) must convert into true stress strain in order to transfer it during simulation (field). Power law is the formula used to convert engineering stress strain to true stress strain. Ultimate strength of APIX42 is predicted at 612 MPa. For modelling part, one quarter of pipeline geometry need to design in MSCPatran software. This study is only focussed on single type of defect. Meshing (element) steps continues after one quarter of geometry is designed. Modelling and simulation is repeated for the different depth (25%, 50% and 75%) of defects and increment in pre-strain. Result obtained after the simulation process must be interpolated to get more accurate failure pressure. Predicted failure pressure is higher for pipeline without presence of pre-strain. Pipeline with the presence of pre-strain, predicted failure pressure is reducing as the amount of pre-strain applied is increases. Three industry models are compared with the finite element result (FEA) for validation. For the lower depth, FEA failure prediction is the highest followed by DNV-RP-F101. ASME B31G and Modified B31G predicted almost same failure pressure but less than FEA and DNV-RPF101. When the depth increases, DVN-RP-F101 predicted higher value of burst pressure compared to FEA. Whereas Modified B31G and ASME B31G predicted lower failure pressure but getting closer to FEA and DVN-RP-F101. The same phenomena happened when various amount of pre-strain (1kN, 3kN and 5kN) applied, but predicted failure pressure is lower than without pre-strain. By referring to the result, presence of pre-strain is really effected value of failure pressure. Increase in pre-strain will cause losing balance strength in pipelines and leads failure in short time compare to pipelines without pre-strain.